2016
DOI: 10.1111/josh.12454
|View full text |Cite
|
Sign up to set email alerts
|

Hand Hygiene Program Decreases School Absenteeism Due to Upper Respiratory Infections

Abstract: Use of hand sanitizer plus handwashing with soap accompanied by educational support is an effective measure to reduce absenteeism due to URIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…Upper respiratory tract and gastrointestinal infections are common infectious diseases in childcare settings [ 1 , 2 , 3 ]. Children under center care are more susceptible to contracting pathogens than children who stay at home due to frequent physical contact [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upper respiratory tract and gastrointestinal infections are common infectious diseases in childcare settings [ 1 , 2 , 3 ]. Children under center care are more susceptible to contracting pathogens than children who stay at home due to frequent physical contact [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Children are prone to place things in their mouths, eat with their hands, and pick their noses [ 6 , 7 , 8 ]. Proper hand hygiene (HH) practice can effectively reduce the incidence of upper respiratory infection; diarrhea; and/or hand, foot, and mouth disease (HFMD) among children in childcare settings, thereby reducing absenteeism associated with these illnesses [ 1 , 2 , 5 , 9 ]. HFMD, for example, is a widespread pediatric disease that has become an endemic childhood disease in East and Southeast Asia.…”
Section: Introductionmentioning
confidence: 99%
“…() stated that more than 50% of children attending a daycare center were not able to wash their hands because there was no soap within their reach, no towel, and no appropriate hand hygiene facilities, and they were at risk for preventable infections. Studies on hand hygiene that have investigated hygiene‐related factors found a correlation between hand hygiene and gastrointestinal as well as respiratory system infections (Aiello, Coulborn, Perez, & Larson, ; Azor‐Martinez et al., ; Curtis & Cairncross, ; Dreibelbis et al., ). Recent studies on the epidemiology of infectious diseases have focused on hand hygiene in places such as hospitals, schools, and homes (Ban et al., ; Dreibelbis et al., ; Willmott et al., ).…”
mentioning
confidence: 99%
“… 8 However, the results of our study correspond with the reduction of upper respiratory infections by providing soap or alcohol-based sanitizers in addition to the education. 7 - 9 , 15 , 17 Bowen et al and Azor-Martínez et al revealed a statistically significant reduction by 38% in the absence rate due to URIs in the intervention group who received education about hand hygiene as well as used hand sanitizers and soap bars that were distributed in the schools, respectively. 7 , 9 , 17 The 12-week intensive hand hygiene campaigns reduced the absence due to ILI by 18% among primary school students in Cairo, Egypt, in 2008.…”
Section: Discussionmentioning
confidence: 95%
“… 7 - 9 , 15 , 17 Bowen et al and Azor-Martínez et al revealed a statistically significant reduction by 38% in the absence rate due to URIs in the intervention group who received education about hand hygiene as well as used hand sanitizers and soap bars that were distributed in the schools, respectively. 7 , 9 , 17 The 12-week intensive hand hygiene campaigns reduced the absence due to ILI by 18% among primary school students in Cairo, Egypt, in 2008. 8 Meanwhile, Sandora et al 18 did not reveal a significant reduction in absence due to URIs after providing hand sanitizers and desk disinfection wipes to school students.…”
Section: Discussionmentioning
confidence: 95%